Chilled foods : a comprehensive guide - Stringer, Michael, 1950-; Dennis, C. (Woodhead Publishing in food science and technology., 2000)
Examines aspects of the chilled food industry including the market, applicable legislation, variety selection, refrigeration, temperature control, quality and safety, microbiology, and shelf-life.